Spatial and temporal pattern of forest carrying capacity and its influencing factors in China, Japan, and Korea based on climate change - Hao, Yidan; Chou, Jieming; Zhao, Weixing; Li, Yuanmeng; Jin, Haofeng (Frontiers in Forests and Global Change, 2024)
Forest carrying capacity is a key factor related to resources, environment, and socio-economic development, and is also an important indicator for measuring the sustainable development capacity of regional society. Previous research has focused more on the management, protection, and utilization of forest resources by sovereign states, and regional assessments of sustainable development management between countries are not common. This study aims to explore the spatial–temporal distribution pattern of regional forest carrying capacity in Northeast Asia, and quantitatively evaluate the forest carrying capacity levels of China, Japan, and South Korea by establishing a comprehensive evaluation framework based on the Pressure-State-Response (PSR) model. We analyzed 16 evaluation indicators from 2010 to 2020 and compared the spatiotemporal distribution of forest carrying capacity in the three countries. The research results indicate that Japan and South Korea maintain a high-pressure and high carrying capacity state, while China exhibits a spatial pattern of high in the west and low in the east. The region with the lowest carrying capacity is Tianjin (with a score of 1.28 in 2010 and 1.44 in 2020). The carrying capacity of forests in China shows a positive spatial correlation, and there is a high concentration of carrying capacity in the northwest region. Therefore, it is necessary to develop targeted forestry management policies to address regional imbalances and strengthen the practice of sustainable forest management in Northeast Asia.